Morfología de las estructuras reproductoras y germinación de nueve especies forestales nativas de Costa Rica - Moreira G., Ileana (1994)
The morphological studies of forest land species let us learn about some basic aspects such as fruit type, parts of the seed and pollination type, that are essential to understand the behavior and their post-management. The present article describes the flowers, fruit and seed morphology as well as their germination of nine forest species from the lower zones of our country (0-1200 m.a.s.l.). The studied species are: Calophyllum brasiliensis (Guttiferae), Cordia alliodora (Boraginaceae), Goethalsia neiantha (Tiliaceae), Hieronyma oblonga (Euphorbiaceae), Stryphnodendron microstachyum (Leguminosae), Terminalia amazonia (Combretaceae), Vochysia ferruginea (Vochysiaceae), Wochysia guatemalensis (Vochysiaceae), Zanthoxylum mayanum (Rutaceae). The material was collected mainly in the Atlantic Zone and in the Huetar Region North of Costa Rica. It was collected vegetative and reproductive samples (fruit flowers and seeds) to be analysed using fresh material. Another part of the material was processed with the scanning electronic microscopy and the ligth microscopy (paraffin innersion). Many drawing and pictures of the collected material were taken for every sample.